An empirical investigation of environmental impacts of agglomeration economies in major cities of Pakistan - Naghmana Ghafoor; Mehr-un-Nisa; Gul Zareen Ghafoor; Faiza Sharif (Scientific Reports)
Abstract Agglomeration economies arise when firms and people co-locate in cities. These economies are determined by city’s activity, size, land and labor prices, and affect the overall environmental conditions of cities in developing economies. The present study empirically investigates environmental impacts of agglomeration economies in major cities of Pakistan during 2002–2019, using Dynamic Fixed Effects (DFE), Pooled Mean Group (PMG), and Mean Group (MG). The findings of the MG model reveal that over the time, the physical environment is negatively affected by agglomeration economies; e.g. population increase (−1.89, p < 0.05), increase in number of factories (−7.11, p < 0.001), increased number of registered vehicles (−1.02, p < 0.05), by creating pressures on human health, civic amenities, and air quality of cities. The study suggests decentralization of big cities, and reshaping of medium and small cities to control population pressure and industrial pollution in major cities of Pakistan.